Ecos de um Brasil francófono : a língua francesa no Colégio de Aplicação da Universidade de Sergipe (1960-2013) - Santos, Ricardo Costa dos (2020)
This work aims to study the presence of the French language in the curriculum of the Application Middle and High School of the Federal University of Sergipe (Codap/UFS), with a time frame from 1960 - the period in which the discipline began to be taught, to 2013 - moment when, after a long discussion about the permanence or not of French, the language was consolidated due to the approval of a selection process to hire an effective teacher, making Codap the only basic education institution in the State of Sergipe to preserve it. The study is based on the concepts of School Discipline by Chervel (1988, 1990), School Culture by Felgueiras (2010), Cultural Capital, Symbolic Capital, Social Capital and Field by Bourdieu (2002, 2004). In the same way, the interview technique is used, as a methodology of History to enable the crossing of data in the construction of the study, according to Meihy (2017). We used sources such as the Minutes of Final and Partial Results, Minutes of Meetings, photographs, reports, among other documents. The research was carried out in the following places: Central Archive of the Federal University of Sergipe AC/UFS, Center for Memory and Documentation of the Application Middle and High School (Cemdap), Archive of the French Alliance of Aracaju, in addition to the personal files of former professors and ex Codap/UFS students. It was proved that the permanence the French language in the curriculum was possible, above all, because it is an Application School, a place marked by the sociability relationship between graduation and school. This thesis contributes to discussions in the areas of History of Education in Sergipe and Brazil, especially in the field of School Disciplines and in the History of the Application Middle and High Schoo